The Role of Self-Compassion and Psychological Hardiness in predicting Social Adjustment in students - Moradgholi, Nosrat; Moradgholi, Mohammad Javad; Bavaghar Zamee, Esmat (Iranian Journal of Neurodevelopmental Disorders, 2023)
Introduction and purpose: It is very necessary to identify the factors that can improve the level of social adaptation of students; Therefore, the present study was conducted with the aim of investigating the role of self-compassion and psychological hardiness in predicting social adjustment. Materials and methods: The present study was a descriptive correlational study. The research population included all secondary school students of the two Zahedan region in the academic year of 2021-2022, based on Gujarsi and Morgan’s table, 290 people who volunteered to participate in the research were selected by available sampling method. And they responded to the questionnaires of self-compassion by Neff (2003), psychological hardiness by Kiamrai et al. (2004) and social adjustment by Sinha and Singh (1993). To analyze the data, Pearson’s correlation test and multiple linear regression analysis were used step by step with SPSS version 22 software. Results: The results showed that there is a positive and significant relationship between self-compassion (r=0.67) and psychological hardiness (r=0.56) with social adjustment (P